Porcine Models of Biofilm Infections with Focus on Pathomorphology - Jensen, Louise K.; Johansen, Anne S. B.; Jensen, Henrik E. (Frontiers in Microbiology, 2017)
Bacterial biofilm formation is one of the main reasons for a negative treatment outcome and a high recurrence rate for many chronic infections in humans. The optimal way to study both the biofilm forming bacteria and the host response simultaneously is by using discriminative, reliable and reproducible animal models of the infections. In this review, the advantages of in vivo studies are compared to in vitro studies of biofilm formation in infectious diseases. The pig is the animal of choice when developing and applying large animal models of infectious diseases due to its similarity of anatomy, physiology and immune system to humans. Furthermore, conventional pigs spontaneously develop many of the same chronic bacterial infections as seen in humans. Therefore, in this review porcine models of five different infectious diseases all associated with biofilm formation and chronicity in humans are described. The infectious diseases are: chronic wounds, endocarditis, pyelonephritis, hematogenous osteomyelitis and implant-associated osteomyelitis.